2012
DOI: 10.1177/230949901202000207
|View full text |Cite
|
Sign up to set email alerts
|

Screw and Wire Fixation for Lisfranc Fracture Dislocations

Abstract: purpose. To assess mid-term outcome of screw and wire fixation for Lisfranc fracture dislocations to determine the risk factors of post-traumatic arthritis. Methods. 15 men and 4 women aged 21 to 58 (mean, 41) years with Lisfranc fractures underwent open/ closed reduction and internal fixation (using screw and wire). Fractures were classified as homolateral (n=7), isolated (n=7), and divergent (n=5). Six patients had open fractures; 8 patients injured 5 tarsometatarsal joints; and 6 patients had pure ligamento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 40 publications
(59 reference statements)
0
15
0
Order By: Relevance
“…5 Despite nerve injury being a documented risk of this procedure, the rate of injury to the deep peroneal nerve has not been previously published in the literature. 3,4 This study allows for more accurate surgical consent of patients, with them being able to be informed that the rate of nerve injury is 11% for primary fixation of the Lisfranc complex, and if routine removal of hardware is planned, the overall rate of injury from both operations is 23%. Furthermore, patients who are undecided about whether to proceed with hardware removal after the primary surgery can be informed that the risk of nerve injury is 15% from the second operation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Despite nerve injury being a documented risk of this procedure, the rate of injury to the deep peroneal nerve has not been previously published in the literature. 3,4 This study allows for more accurate surgical consent of patients, with them being able to be informed that the rate of nerve injury is 11% for primary fixation of the Lisfranc complex, and if routine removal of hardware is planned, the overall rate of injury from both operations is 23%. Furthermore, patients who are undecided about whether to proceed with hardware removal after the primary surgery can be informed that the risk of nerve injury is 15% from the second operation.…”
Section: Discussionmentioning
confidence: 99%
“…5 Although some studies have reported that no patient developed a painful neuroma, the true rates of actual nerve injury (absent, altered, or painful sensation) have not been documented. 3,4 The current study investigated the rate of deep peroneal nerve symptoms following primary surgery and also after hardware removal for Lisfranc injuries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There may only be ligamentous injury, but if there is also direct bone injury, then it is easily diagnosed at the initial stage [7,8]. However, when the ligamentous complex is also damaged or a bone is injured alone, missed diagnosis or misdiagnosis can occur and lead to chronic pain and walking disorders after convalescence [9][10][11]. Open reduction and internal fixation are generally recommended for the treatment of Lisfranc joint injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have proven that the Lisfranc ligament has the maximum width, thickness and cross-sectional area of all these ligaments, so its ultimate load is far higher than the others. 19 Reconstruction of the Lisfranc ligament is of great importance for the function of the foot. At present, the Lisfranc ligament is most commonly repaired by hollow countersunk screw inserted from the medial cuneiform to the second metatarsal base.…”
Section: Discussionmentioning
confidence: 99%